REDESIGNING INNOVATIVE PRODUCTS OF UP-CYCLE-BASED MINDI WOOD WASTE FASHION BAGS IN KREBET, BANTUL-YOGYAKARTA - Susanto, Moh. Rusnoto; Setiadi, Bayu Rahmat; Purbasari, Mita; Lusiana, Lusiana; Hasa, Zainul Faizien; Susatyo, Rudy; Handoyono, Nurcholish Arifin; Arumsari, Mela Dina; Selimanorita, Shafa’; Putrianti, Flora Grace (International Journal of Engagement and Empowerment (IJE2), 2024)
In the industrial era 4.0 towards Society 5.0, the Indonesian government is currently intensively advancing the creative industry. Yogyakarta needs to improve its marketing management system and human resources to be strong and competitive as a storehouse of creative people and the target of world tourist destinations. Currently, creative industries have the opportunity to process local raw materials into functional products that are globally competitive. The Up-Cycle product is a fashion bag made from processed mindi wood that emphasizes the image. We are redesigning a distinctive fashion bag while maintaining the quality and uniqueness of the product in visual form, material processing, and style. The objectives of this study include (1) Redesigning fashion bag products based on up-cycle mindi processed wood waste, which can be effective in creating new, competitive SME products. (2) Implementation of the Redesign strategy through the PRN BRIN research program can build access to improving the quality of creative human resources for RUAYA SMEs as a manufacturer of UP-Cycle-based Mindi Wooden Fashion Bags in Krebet, Bantul. Applied research methods, such as R&D through a practice-based research approach by the research roadmap, focus on 'practice-based' and several empirical experiences carried out by practitioners, such as artists, designers, and innovative. Redesigning development practitioners. This research explores data through visual documentation and notes of creative practitioners to seek new understanding and find new techniques to realize ideas that can be put into practice in creating new forms of creative products, as well as visionary creative strategies that are expected to improve quality. Targeted research results include: (1) Creating design innovation through optimizing the UP-CYCLE product redesign program. Fashion bags made from processed mindi wood waste can be carried out effectively to encourage increased value for both MSMEs and their products. (2) Implementing Redesign results on RUAYA UKM products that are more highly competitive